Hitting the moving target: modelling ontogenetic shifts with stable isotopes reveals the importance of isotopic turnover. (May 2016) - Hertz, Eric; Trudel, Marc; El‐Sabaawi, Rana; Tucker, Strahan; Dower, John F.; Beacham, Terry D.; Edwards, Andrew M.; Mazumder, Asit
Summary: Ontogenetic niche shifts are widely prevalent in nature and are important in shaping the structure and dynamics of ecosystems. Stable isotope analysis is a powerful tool to assess these shifts, with δ 15 N providing a measure of trophic level and δ 13 C a measure of energy source. Previous applications of stable isotopes to study ontogenetic niche shifts have not considered the appreciable time lag between diet and consumer tissue associated with isotopic turnover. These time lags introduce significant complexity into field studies of ontogenetic niche shifts. Juvenile Chinook salmon ( Oncorhynchus tshawytscha ) migrate from freshwater to marine ecosystems and shift their diet from feeding primarily on invertebrates to feeding primarily on fish. This dual ontogenetic habitat and diet shift, in addition to the long time lag associated with isotopic turnover, suggests that there is potential for a disconnect between the prey sources that juvenile salmon are consuming, and the inferred prey sources from stable isotopes. We developed a model that considered ontogenetic niche shifts and time lags associated with isotopic turnover, and compared this 'ontogeny' model to one that considered only isotopic turnover. We used a Bayesian framework to explicitly account for parameter uncertainty. Data showed overwhelming support for the ontogeny model relative to the isotopic turnover model. Estimated variables from best model fits indicate that the ontogeny model predicts a much greater reliance on fish prey than does the stomach content data. Overall, we found that this method of quantifying ontogenetic niche shifts effectively accounted for both isotopic turnover and ontogenetic diet shifts; a finding that could be widely applicable to a variety of systems. Abstract : Stable isotopes are commonly used to study ontogeny, but isotopic turnover, which has the potential to give misleading results, has not often been considered. The authors developed a model to consider ontogeny and isotopic turnover, and show the novel insights that such an approach can bring in a case study on juvenile salmon.